CALVING DYNAMICS OF TWO OUTLET GLACIERS OF THE SOUTH PATAGONIAN ICEFIELD DERIVED FROM TERRASAR-X AND TANDEM-X - Johnson Gavilan, Erling John; Floricioiu, Dana (My University, 2019)
We estimate the calving flux of two major outlet glaciers belonging to the South Patagonian Icefield (SPI), Perito Moreno and Upsala Glaciers, between 2011 and 2015 comparing it to the correspondent total mass balance in a similar time period (2012-2016). Additionally, time series of calving rates are calculated back to 2008, allowing a detailed analysis of the frontal advance/retreat and velocity change of these glaciers.
Keywords: glacier; calving flux; calving rate; mass balance